The Effect Of Rating Errors Towards The Effectiveness Of Performance Appraisal - Sabrina, Nasser Khan; Rusli, Ahmad; Sopian, Bujang (2011)
The aim of this paper is to explore the effect of rating errors towards the effectiveness of performance appraisal. This research studies the informants knowledge on rating errors, the effect of halo effect, leniency and central tendency towards the effectiveness of performance appraisal and ways that could be taken to solve and prevent rating errors. The organization that is chosen for this study is one of the government agencies in Malaysia. This study used qualitative approach and in-depth interview used to collect the data. Four (4) informants involves in this study. The data was analyzed by using content analysis technique. The findings ofthis study stated that rating errors such as halo effect, leniency and central tendency has a negative effect towards the effectiveness of performance appraisal. This study suggests that the raters should be train on rating errors and measurement in order to have appropriate understanding on performance appraisal and to avoid rati ng biases and inaccu racies. Moreover, em ployee feedback is also necessary to avoid rating errors by giving their opinions and comments on their rating results. This study also provides a strong basis for further research on performance appraisal rater especially on cognitive modeling of a rater while conducting performance appraisal. In conclusion, this research would benefit the employees and the organization by identifying underlying factors which may jeopardize the effectiveness of performance appraisal. With a fair and just performance appraisal exercise, it would increase the moral and commitment of employees to the organization. The implications of this study to theory and practice, conceptual and methodological limitations as well as directions for future research also are discussed.